2003
DOI: 10.1051/0004-6361:20030696
|View full text |Cite
|
Sign up to set email alerts
|

The post-AGB evolution of AGB mass loss variations

Abstract: Abstract. We present new numerical hydrodynamical modelling of the evolution of Asymptotic Giant Branch (AGB) mass loss fluctuations during the post-AGB/Planetary Nebula phase. These models show that after ionization, the observable effects of the mass loss fluctuations disappear in a few thousand years, consistent with the fact that only few PNe have been found to be surrounded by "rings". We derive the observational characteristics of these rings, and compare them to reported observations of the rings around… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(48 reference statements)
3
9
0
Order By: Relevance
“…Garcia‐Segura, Lopez & Franco (2001), on the other hand, point out that where there are changes in the polarity of the progenitor magnetic field, and where the stellar wind is also magnetized, then this would lead to pressure oscillations which drive circularly symmetric compressions into the outflowing winds. Their results are startlingly similar to those observed for He 2−90, although it has been suggested that the magnetic dynamo cycle in AGB stars would be much shorter than that corresponding to the rings (Meijerink et al 2003).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Garcia‐Segura, Lopez & Franco (2001), on the other hand, point out that where there are changes in the polarity of the progenitor magnetic field, and where the stellar wind is also magnetized, then this would lead to pressure oscillations which drive circularly symmetric compressions into the outflowing winds. Their results are startlingly similar to those observed for He 2−90, although it has been suggested that the magnetic dynamo cycle in AGB stars would be much shorter than that corresponding to the rings (Meijerink et al 2003).…”
Section: Introductionsupporting
confidence: 75%
“…This leads to appreciable changes in the pressure and density characteristics of these regimes, and wipes out much of the evidence relating to later phases of AGB mass loss (e.g. Meijerink et al 2003;Perinotto et al 2004;Schönberner et al 2005, Mellema 1994).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Neither the morphology at different spatial scales nor the motions detected very close to the center can be satisfactory explained by current models on the mass-loss mechanisms in AGB stars and their typical time-scales. For instance, Sandin & Höfner (2004 and references therein) have predicted shell density distributions not compatible with those observed around IRC+10216 (see also on the same topic Meijerink et al, 2003). Another scenario for the formation of the shells in a spherically symmetric stellar wind has been explored by Soker (2000Soker ( , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…In the current decade, thanks to the operations of high--sensitivity millimeter/submillimeter telescopes (e.g., ALMA, JVLA), the new detection of such patterns and their theoretical understanding have led to significant and synergistic progress. the patterns disappearing within ∼ 3000 years after ionization starts (Meijerink et al 2003). With the relevant model development (see §2) and the timescales consistent with the orbital periods of wide binaries, it is now commonly accepted that binary companions are responsible for modulating the mass distribution of CSEs in the recurrent form.…”
Section: Introductionmentioning
confidence: 96%